2021
DOI: 10.3389/fcell.2021.667412
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Levels of miR-144-3p Induce Cholinergic Degeneration by Impairing the Maturation of NGF in Alzheimer’s Disease

Abstract: Cholinergic degeneration is one of the key pathological hallmarks of Alzheimer’s disease (AD), a condition that is characterized by synaptic disorders and memory impairments. Nerve growth factor (NGF) is secreted in brain regions that receive projections from the basal forebrain cholinergic neurons. The trophic effects of NGF rely on the appropriate maturation of NGF from its precursor, proNGF. The ratio of proNGF/NGF is known to be increased in patients with AD; however, the mechanisms that underlie this obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 59 publications
(63 reference statements)
1
5
0
Order By: Relevance
“…The Hisayama Study ( 35 ) reported increased odds of all-cause dementia, Alzheimer’s disease, and vascular dementia in relation to elevated 2h-PG, rather than FPG. Given the fact that memory loss is the key symptom of Alzheimer’s disease ( 36 ), our study, which showed 2h-PG negatively associated with memory, supports results derived from the Hisayama Study.…”
Section: Discussionsupporting
confidence: 88%
“…The Hisayama Study ( 35 ) reported increased odds of all-cause dementia, Alzheimer’s disease, and vascular dementia in relation to elevated 2h-PG, rather than FPG. Given the fact that memory loss is the key symptom of Alzheimer’s disease ( 36 ), our study, which showed 2h-PG negatively associated with memory, supports results derived from the Hisayama Study.…”
Section: Discussionsupporting
confidence: 88%
“…35 Additionally, the degeneration and loss of BFCNs have been described in some animal models of AD. [36][37][38][39] The hippocampus primarily receives dense cholinergic projections from the MS and VDB nuclei of the basal forebrain, forming the basal forebrain hippocampal circuit. 40 release regulates learning and memory processes by generating GABAergic inhibition of hippocampal dentate granule cells via astrocyte intermediaries.…”
Section: Discussionmentioning
confidence: 99%
“…Using post‐mortem MRI and histopathology, a recent study detected volume decrease and microstructural integrity degeneration in the nucleus basalis of Meynert (NBM) of AD patients, and the decreased BFCN density was associated with reduced cholinergic tracts to its projection cerebral areas 35 . Additionally, the degeneration and loss of BFCNs have been described in some animal models of AD 36–39 . The hippocampus primarily receives dense cholinergic projections from the MS and VDB nuclei of the basal forebrain, forming the basal forebrain hippocampal circuit 40 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These evidence may further explore the importance of miR-144 in connection with metabolic function and neurodegenerative diseases including PD. In addition, the involvement of miR-144 in inducing cholinergic degeneration by impairing the maturation of nerve growth factor in Alzheimer's Disease has been revealed in experimental models (Zhou et al, 2021). Although more research is necessary to understand the role of miR-144, evidence from literature provides a mechanistic link of miR-144 in obesity associated neurodegenerative disorders.…”
Section: Mir-144mentioning
confidence: 99%